A predictive toxicology approach to characterize potential respiratory effects of functionalized nanocellulose fibres in a co-culture system - Ventura, Célia (2020)
Cellulose nanofibrils (CNF) have an enormous potential for industrial and biomedical applications, assuming a great economic value. Because other nanofibres, e.g. carbon nanotubes (CNT), have revealed toxicity 1,2, there is a need to comprehensively evaluate the toxic potential of CNF along the value chain, before they enter the market. This project is aimed at a safety evaluation of several CNF comparatively to CNT, in a co-culture of human-derived alveolar epithelial cells and macrophages3. A predictive toxicology approach is used, i.e., the toxicity will be characterized alongside the specific fibre-associated mode of action, including immunotoxicity, genomic and epigenetic effects. The data obtained for two CNF synthesized from Eucalyptus gobulus but using different pre-treatments will be presented. Future work includes the use of omics-based tools adapted to the toxicity assessment of CNF and other NMs that will give some insights on cellular and molecular mechanisms underlying CNF toxicity. The overall results will be used to ensure the safety of these CNF or to allow the modification of toxic CNF in order to reduce the adverse outcomes, thereby complying with the safer-by-design approach.